Thermal properties and water absorption study of thermoplastic starch film reinforced with rice husk biochar: article / Muhammad Amirul Adeeb Mohd Zaine, Suhaila Sauid - Mohd Zaine, Muhammad Amirul Adeeb; Sauid, Suhaila (2017)
The aim of this study was to analyse thermal properties and water absorption of thermoplastic starch reinforce with rice husk biochar. The sample was prepared by using a conservative casting technique by blending starch with plasticizer, sulphur, acetic acid, and rice husk biochar. As observed, FTIR was used to investigate the chemical interaction between the different components. Water absorption of the film was tested under room temperature with an ambient humidity. As a result it showed that thermoplastic starch without any reinforcement rice husk biochar have the highest percentage of water absorption which is 45.23% while with 7% concentration of rice husk biochar give the lowest percentage of water absorption of 27.37%. The analysis of thermoplastic starch included with the increment of the rice husk biochar concentration to the thermoplastic starch it showed that the percentage of water absorb decreases. The behaviour of thermal properties f thermoplastic starch with rice husk biochar was investigated by using thermogravimetric analysis (TGA) and as a result the thermal stability seems to be increasing with the increasing of rice husk biochar concentration. However the sample with 5% of rice husk bioichar seems to undergo the highest rate of mass change. This indicates that it goes through an easier thermal degradation